Determinación de calcio sérico en mujeres multíparas de la asociación primero de mayo del cantón chambo, como ayuda diagnóstica de osteopenias - Pazmiño Pérez, Vannesa Cristina. (2010)
The sérico calcium determination in the women multíparas of the association first of May of the Chambo corner is important because it allows to know the concentration Ca++ that is the main extracellular bivalent cation reacts to hormonal stimuli, electrical or mechanical, a temporary increase of the flow of Ca2+ increasing his concentration which allows interactions with proteins of union of Ca2+ you specify, which they activate many processes. The Ca2+ is essential for important processes, among them neural excitabilidad, liberation of neurotransmitter, muscular contraction, membrane integrity and coagulation of the blood